2017
DOI: 10.31235/osf.io/rvyz3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When Equity Matters for Marital Stability: Comparing German and American Couples

Abstract: Comparing West Germany and the United States, we analyze the association between equity - in terms of the relative gender division of paid and unpaid work hours – and the risk of marriage dissolution. Our aim is to identify under what conditions equity influences couple stability. We apply event-history analysis to marriage histories using data from the German Socio-Economic Panel for Western Germany and the Panel Study of Income Dynamics for the United States for the period 1986 to 2009. For the United State… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
3
6
0
Order By: Relevance
“…Our results would suggests that dissolution is associated with movements away from this specific arrangement -both egalitarian and equitable -and not from any type of egalitarian arrangement as found by Kalmijn et al (2007). This finding is in line with the effect that Bellani et al (2018) found for all couples in the USA, where women's double shift had a destabilising effect. For marriages, we did not find support for our hypothesis, as there was no association of traditionalism or inequity and risks of dissolution.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our results would suggests that dissolution is associated with movements away from this specific arrangement -both egalitarian and equitable -and not from any type of egalitarian arrangement as found by Kalmijn et al (2007). This finding is in line with the effect that Bellani et al (2018) found for all couples in the USA, where women's double shift had a destabilising effect. For marriages, we did not find support for our hypothesis, as there was no association of traditionalism or inequity and risks of dissolution.…”
Section: Discussionsupporting
confidence: 86%
“…For the USA, Amato et al (2003) have shown that men's participation in domestic work increased marital happiness for women but had the reverse effect on men, but Wilcox and Nock (2006) did not find this effect to be significant. For the same country, Bellani et al (2018) find that, if the division of paid and unpaid work underbenefits women, it has a destabilising effect for them, especially if both partners work similar hours; however, the authors did not find the same effect for Germany. In Sweden, Ruppaner et al (2018) found that men's involvement in domestic work was associated with lower risks of dissolution.…”
Section: Divisions Of Work and Union Stabilitymentioning
confidence: 87%
See 1 more Smart Citation
“…The classical framework of Equity Theory also provides insight and support for our predictions (e.g., Bellani et al, 2018;Hatfield & Traupmann, 1981). A basic proposition of the theory-which draws from exchange and social comparison theories-is that individuals feel distress when perceiving inequity in relationships with others (Huseman et al, 1987).…”
Section: Power Asymmetry and Inequity In Romantic Relationshipssupporting
confidence: 59%
“…A basic proposition of the theory—which draws from exchange and social comparison theories—is that individuals feel distress when perceiving inequity in relationships with others (Huseman et al, 1987). In marital relationships, those who feel equitably treated in their marriages report greater relationship satisfaction, relationship stability, and sexual satisfaction (Bellani et al, 2018; Hatfield et al, 1982; Utne et al, 1984). The present research extends these literatures of power asymmetry and inequity by examining how SES inequality—a construct closely related to, yet distinct from power inequality or inequity (for conceptual distinctions, see Kraus et al, 2012)—within romantic relationships predicts relationship quality.…”
Section: Power Asymmetry and Inequity In Romantic Relationshipsmentioning
confidence: 99%